2018
DOI: 10.1049/iet-cds.2017.0324
|View full text |Cite
|
Sign up to set email alerts
|

Low‐power design for DC current transformer using class‐D compensating amplifier

Abstract: Classical DC current transformer, based on a linear amplifier as a compensating amplifier, is well known as a power inefficient device. If the linear amplifier is replaced with switching counterpart, significant power saving can be achieved. A natural choice for replacement can be found in a half-bridge class-D amplifier. However, the half-bridge class-D amplifier is prone to bus-pumping effect, and direct replacement cannot be performed in a straightforward manner. This study presents an analysis of power con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…If the internal SWT dissipation, related to I1 and I2, is not large enough, problem occurs, since unidirectional power supply is incapable to absorb negative 1 D I or 2 D I . The problem is similar to well-known effect in theory of audio amplifiers, named as buss pumping effect [15]. In that situation, power bus with negative supply current increases voltage level, increasing in a same time internal consumptions inside of the SWT, in order to dissipate energy returned from the secondary winding.…”
Section: I I mentioning
confidence: 74%
See 1 more Smart Citation
“…If the internal SWT dissipation, related to I1 and I2, is not large enough, problem occurs, since unidirectional power supply is incapable to absorb negative 1 D I or 2 D I . The problem is similar to well-known effect in theory of audio amplifiers, named as buss pumping effect [15]. In that situation, power bus with negative supply current increases voltage level, increasing in a same time internal consumptions inside of the SWT, in order to dissipate energy returned from the secondary winding.…”
Section: I I mentioning
confidence: 74%
“…could overcame SWT limitations, but in practice their complexity and efficiency are reasonable for much higher powers then powers found in DCTs. Absorption of negative current of power is certainly possible to be solved by more or less complex electronics [15], but in this case the question arises of what is being obtained and what is lost, which is an analysis that goes beyond the scope of this paper. Power consumtion of two transducer types IT and SWT.…”
Section: Discussionmentioning
confidence: 99%
“…As the dependence of the second harmonic component voltage on the DC current is non-linear, fluxgate current sensors usually work in the feedback loop compensating the measured DC current to zero. These sensors are also called DC current transformers [72], [73], [74]. We have shown that this mechanism can be used on a standard current transformer by injecting the excitation current into the secondary winding [75].…”
Section: Fig 3 Rogowski Coil Integrated Into the Laminated Busbar -Amentioning
confidence: 99%
“…For DC current measurement, current transformer based on diverter principle and zero flux DC current transformer are widely used [10]- [12]. Although these transformers feature high measurement accuracy, its large volume and heavy weight restrict their practical field applications on site.…”
Section: Introductionmentioning
confidence: 99%